Deposition of ITO thin films onto PMMA substrates for waveguide based biosensing devices - Azevedo, Sofia (2012)
Biosensors’ research filed has clearly been changing towards the production of multifunctional and innovative design concepts to address the needs related with sensitivity and selectivity of the devices. More recently, waveguide biosensors, that do not require any label procedure to detect biomolecules adsorbed on its surface, have been pointed out as one of the most promising technologies for the production of biosensing devices with enhanced performance. Moreover the combination of optical and electrochemical measurements through the integration of transparent and conducting oxides in the multilayer structures can greatly enhance the biosensors’ sensitivity. Furthermore, the integration of polymeric substrates may bring powerful advantages in comparison with silicon based ones. The biosensors will have a lower production costs being possible to disposable them after use (“one use sensor chip”). This research work represents a preliminary study about the influence of substrate temperature on the overall properties of ITO thin films deposited by DC magnetron sputtering onto 0,5 mm thick PMMA sheets.